Inovasi Pembelajaran Pendidikan Agama Islam dalam Menanamkan Prinsip Ekonomi Syariah di Era Digitalisasi - Al Bazzar; Anas Anas; M. Rafid Marwal (ALSYS, 2026)
Although innovations in Islamic Religious Education (PAI) learning and the development of Islamic economics in the era of digitalization have been widely discussed, studies that specifically examine the integration of digital-based PAI learning in instilling Islamic economic principles contextually and applicatively remain limited. This study aimed to analyze and describe PAI learning innovations in instilling Islamic economic principles in the era of digitalization. This study used a qualitative approach with a case study design, involving 30 participants consisting of 2 PAI teachers and 28 senior high school students selected through purposive sampling. Data were collected through in-depth interviews, observation, documentation, and questionnaires as supporting data, and were then analyzed using thematic analysis through the stages of data reduction, data presentation, and conclusion drawing. The results showed that digital-based learning innovations contributed to improving students’ understanding of Islamic economic concepts, as reflected in their critical thinking skills, active engagement in learning, and strengthening of religious attitudes such as honesty and responsibility. The use of digital media, Islamic transaction simulations, and a problem-based approach also supported the internalization of Islamic economic values in a more contextual and applicative manner. These findings contribute to the development of constructivist theory and digital literacy in PAI learning, while also broadening understanding of technology integration in value-based education. The conclusion of this study confirms the importance of digital-based learning innovation as a strategy for shaping students’ understanding and character in Islamic economics, as well as encouraging teachers and educational institutions to integrate technology systematically into the learning process.